Pharmacokinetics of a novel anti-platelet drug from the glycoprotein IIb/IIIa receptor inhibitors group - S. B. Fitilev; Yu. F. Glukhov; S. V. Lukyanov; V. I. Kazey; I. B. Bondareva; A. V. Vozzhaev; I. I. Shkrebniova; D. A. Kliuev (LLC "Publisher OKI", 2022)
Relevance. As part of the conducted open non-randomized phase I clinical trial the pharmacokinetics (PK) of the first Russian novel antiplatelet agent Angipur (nonpeptide glycoprotein IIb/IIIa receptor inhibitor) was studied.Aim of the research was to evaluate PK parameters of Angipur in healthy volunteers after single dose ascending infusions.Methods. 20 male healthy volunteers were enrolled in this phase I trial. Angipur (0.02% concentrate solution for infusion) was administered to every subject in single doses 0.015, 0.05, 0.09 mg/kg for 3 consecutive days. PK parameters were evaluated.Results. After single intravenous administration of doses 0.015, 0.05, 0.09 mg/kg to healthy volunteers the peak plasma concentration of Angipur was reached at the end of the infusion, and then the plasma concentration rapidly decreased 15 minutes after the end of the infusion followed by slow decrease for 12 hours. Dose proportionality for key PK parameters was established. After single infusions of doses 0.015, 0.05, 0.09 mg/kg mean AUC0-t was 27.11, 92.04 and 180.39 ng× h/ml; mean AUC0-¥ - 37.03, 125.76 and 239.61 ng×h/ml; mean Сmax - 12.44, 46.1 and 92.48 ng/ml; mean Vd - 304.01, 299.67 and 252.96 l; mean Т1/2 - 6.72, 6.84 and 6.06 h; Сl - 32.19, 32.29 and 31.55 l/h; kel - 0.1073, 0.1109 and 0.1257 l/h; MRT - 8.94, 8.93 and 8.18 h.Conclusion. Pharmacokinetics of Angipur in studied doses demonstrated linearity, rapid reaching of Сmax immediately after the infusion and the high distribution of the drug in tissues and biological fluids of the human organism..